Evidence-Based Practice in Irregular Cornea Patients’ Management With Contact Lenses - Raúl Martín Herranz (The Ophthalmology, 2017)
Contact lenses (CLs) are safe and commonly used method to correct the refractive errors. Rigid gas permeable (RGP) CLs are the first option in visual rehabilitation of patients with irregular cornea, helping to further delay surgical treatment and improve patients’ quality of life (QoL). Although, the practice of CLs in patients with irregular cornea must be based on evidence, there is a lack of Clinical Practice Guidelines (CPGs) developed and assessed under high standards as recommended by the Appraisal of Guidelines for Research and Evaluation (AGREE) (http:// www.agreetrust.org/). Current fitting guidelines provided by researchers, practitioners, entities or manufacturers, are generally supported with relatively small clinical studies or cohort studies with owner-designs, providing no-objective pathways to conduct the CL fitting that generally require steep learning curve and practitioners with long experience in CL practice. These recommendations are usually not clinically validated to prove the quality and applicability in new clinical scenarios. CL practitioners require evidence-based guidelines and CPGs that include an objective pathway to choose the CL characteristics like design, geometry, material, etc., with clinically validated support of the recommendations to calculate lens parameters such as back optic zone radius, lens diameter and lens geometry. This practice should be based on clinical research with prospective, randomized and well-designed studies (case-control, cohort, or clinical trials studies) that have been developed and assessed under high standards (AGREE). These new evidence-based guidelines or CPGs will not only improve the safety and transparency of CL fitting procedures, but also guarantee the best patient care with less cost to patients with irregular cornea requiring RGP, improving their vision and QoL.